A genre analysis of Christian sermons in the Filipino-Chinese community in Metro Manila - Liu, Chunping (Paul) (Animo Repository, 2005)
This paper investigated the generic structure and lexico-grammatical features in Christian sermonic discourse and argued that ministers observe certain conventions in constructing their sermons. By analyzing a number of sermon samples, the researcher found that typical patterns of organizational moves and sub-moves or structural elements exist across sermons delivered by different Filipino-Chinese ministers from different church groups. Some salient lexico-grammatical features were also identified in terms of how they function as strategic devices in realizing the overall communicative purpose of sermonic discourse.